Die Protokolle Des cisleithanischen Ministerrates 1867-1918 Band II: 1868-18711. Jänner 1868 − 21. November 1871 - Lein, Richard (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The publication contains the edited minutes of the Cisleithanian Council of Ministers 1868-1871. This period, immediately following the Austro-Hungarian compromise, represents a major reconstruction of the Habsburg Monarchy from the unit Empire Austria (Kaisertum Österreich) into the dualistic monarchy Austria-Hungary. This is also mirrored in the minutes of the Council of Ministers. Being one of the highest institutions of the state this concil had to deal with a wide range of topics that were prepared for the imperial decision. The publication of the edited minutes opens up a source for further historical research in all fields of sciences, also beyond political historiography (e.g. history of economy, of financial economy, of social sciences, of everyday life, or of technology).